Assessment of the Effectiveness of Simulation and Recitation Training for Traffic Control Volunteers (Supeltas) on Cervical Spinal In-Line Position Stabilization with Helmet Removal Maneuvers - Ferry Efendi (Journal of Global Pharma Technology, 2020)
Motor vehicle traffic accidents are a leading cause of death for an individual in Indonesia. This study aimed to evaluate the effectiveness of training using simulation and recitation models focusing on the achievement of the pre-hospital performance of traffic-control volunteers (Supeltas) in stabilizing cervical spinal in-line position in helmet removal maneuver. This study applied pre-test and post-test design with 248 respondents. Data were collected using questionnaires and evaluation papers to assess volunteers during practical tests. Data statistical analysis procedures included One-Way ANOVA, Wilcoxon-signed rank test, and N-gain score test. Differences were noted in the demographic data with significant findings and effects associated with age (p= 0.041) and education (p= 0.046) of Supeltas in stabilizing the cervical spine. The intervention group exposed to SMT training model showed a difference in the average scores of knowledge (mean 60.85 to 85.67; p= 0.010) and skills (mean 59.80 to 86.81; 0.002), which were greater than the scores of the group receiving RMT (mean 53.65 to 65.06; p = 0.028) and skills (mean 59.20 to 84.73; p= 0.043). The knowledge (N-gain score = 61.35%) and skills (N-gain score= 61.41%) of the group receiving a role-playing model (SMT) increased more effectively, compared to the increase experienced by the group receiving an assignment (RMT) (N-gain score knowledge= 23.57%; skills= 17.29%). This study suggests that the simulation model is more effective than the recitation model in improving the ability of Supeltas in stabilizing the cervical spinal in-line position for helmet removal in trauma situations. Keywords: Recitation, Simulation, Stabilization, Training.